Ornamental Exterior versus Therapeutic Interior of Madagascar Periwinkle (Catharanthus roseus): The Two Faces of a Versatile Herb - Naghmeh Nejat; Alireza Valdiani; David Cahill; Yee-How Tan; Mahmood Maziah; Rambod Abiri (The Scientific World Journal)
Catharanthus roseus (L.) known as Madagascar periwinkle (MP) is a legendary medicinal plant mostly because of possessing two invaluable antitumor terpenoid indole alkaloids (TIAs), vincristine and vinblastine. The plant has also high aesthetic value as an evergreen ornamental that yields prolific blooms of splendid colors. The plant possesses yet another unique characteristic as an amiable experimental host for the maintenance of the smallest bacteria found on earth, the phytoplasmas and spiroplasmas, and serves as a model for their study. Botanical information with respect to synonyms, vernacular names, cultivars, floral morphology, and reproduction adds to understanding of the plant while the geography and ecology of periwinkle illustrate the organism’s ubiquity. Good agronomic practices ensure generous propagation of healthy plants that serve as a source of bioactive compounds and multitudinous horticultural applications. The correlation between genetic diversity, variants, and TIA production exists. MP is afflicted with a whole range of diseases that have to be properly managed. The ethnobotanical significance of MP is exemplified by its international usage as a traditional remedy for abundant ailments and not only for cancer. TIAs are present only in micro quantities in the plant and are highly poisonous per se rendering a challenge for researchers to increase yield and reduce toxicity.